Thematic analysis in selected reading passages of English for Tourism textbooks for university students in Indonesia: From a systemic functional linguistic perspective - Yusuf, Muhammad; Gunawan, Wawan; Ardiasih, Lidwina Sri; Sakhiyya, Zulfa; Albar, Mahmud Arief; Syahputra, Fikry Prastya (Research Journal in Advanced Humanities, 2025)
English for Tourism textbooks play a crucial role in developing students' language skills for the tourism industry. One of the materials in these textbooks is a reading passage. This study aims to investigate how thematic analysis is used in selected reading passages in an English for tourism and hospitality textbook. This study departs from textual function in systemic functional linguistic perspective. This study employed a qualitative content analysis method. The data consisted of five hundred (500) clauses taken from thirteen (13) passages in the textbook of English for Hotel and Tourism. From the analysis, it was found that the types of themes used in the textbook include simple and multiple themes. The simple theme (ST) is realized through the topical theme in the clause. The multiple theme (MT) is represented through the combination of textual ^ topical themes (conjunctive). In terms of markedness of Theme, the variations in the theme were found, including Unmarked Simple Theme (UST), Unmarked Multiple Theme (UMT), and Marked Simple Theme (MST). The variation of the theme helps in organizing the flow of information. The changing of the Theme position (marked or unmarked) can be a sign of important content in focus in the passage.